2010
DOI: 10.1111/j.1476-5381.2010.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression‐resistant endophenotype in mice overexpressing cannabinoid CB2 receptors

Abstract: Background and purpose:The present study evaluated the role of CB2 receptors in the regulation of depressive-like behaviours. Transgenic mice overexpressing the CB2 receptor (CB2xP) were challenged with different types of acute and chronic experimental paradigms to evaluate their response in terms of depressive-like behaviours. Experimental approach: Tail suspension test (TST), novelty-suppressed feeding test (NSFT) and unpredictable chronic mild stress tests (CMS) were carried out in CB2xP mice. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
184
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(197 citation statements)
references
References 65 publications
11
184
0
2
Order By: Relevance
“…Furthermore, this opening of CaCCs is most likely responsible for the observed reduction in neuronal excitability upon CB 2 R activation. The presence of CB 2 R mRNA in the brain and CB 2 Rs in neurons of the brainstem, the cerebellum, and the hippocampus has been reported (12,13,18,(25)(26)(27)(28), but their presence in the cortex remained to be further characterized. The current view on the presence of functional CB 2 Rs in the CNS supports the expression of CB 2 Rs in neurons essentially upon brain stress and damage (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this opening of CaCCs is most likely responsible for the observed reduction in neuronal excitability upon CB 2 R activation. The presence of CB 2 R mRNA in the brain and CB 2 Rs in neurons of the brainstem, the cerebellum, and the hippocampus has been reported (12,13,18,(25)(26)(27)(28), but their presence in the cortex remained to be further characterized. The current view on the presence of functional CB 2 Rs in the CNS supports the expression of CB 2 Rs in neurons essentially upon brain stress and damage (19).…”
Section: Discussionmentioning
confidence: 99%
“…CB 2 Rs are found primarily in the immune system and were initially regarded as the "peripheral" cannabinoid receptor (10,11). This generally accepted idea is challenged by the description of CNS CB 2 R gene expression in rats and wild-type mice (12)(13)(14) and the identification of functional CB 2 Rs on glial cells and neurons (15)(16)(17)(18). In addition to the current view that supports the expression of functional CB 2 Rs in neurons upon brain stress or damage (19), it has been reported that CB 2 Rs could play a role in general CNS physiology (20)(21)(22).…”
mentioning
confidence: 99%
“…Coronal brain sections (500 mm) beginning at plates 19-20 (Paxinos and Franklin, 2001) were obtained in a cryostat (À101C). The PFC, LC, and DR were microdissected according to a modification of the Palkovits method (Palkovits, 1983) as described previously (Garcia-Gutierrez et al, 2010). Total RNA was isolated from brain tissue micropunches using Trizol reagent (Invitrogen, Madrid, Spain) and subsequently retrotranscribed to cDNA.…”
Section: Gene Expression Analysesmentioning
confidence: 99%
“…Further studies in rats have identified CB 2 r distributed extensively throughout different brain areas, including the spinal nucleus, hippocampus, olfactory nucleus, cerebral cortex, amygdala, striatum, thalamus, and cerebellum (Atwood and Mackie, 2010;Gong et al, 2006;Onaivi et al, 2006). In addition, CB 2 r gene expression has been identified in the thalamus, periaqueductal grey matter, cervical and thoracic spinal cord, and different brain nuclei, including the caudateputamen, nucleus accumbens, cingulate cortex, amygdala, hippocampus, ventromedial hypothalamic nucleus, arcuate nucleus, substantia nigra, and dorsal and medial raphe nuclei (Garcia-Gutierrez et al, 2010;Racz et al, 2008).…”
mentioning
confidence: 99%
“…This finding is supported by recent studies demonstrating that systemic administration of the CB 2 R agonist O-1966 inhibited cocaine-induced conditioned place preference in WT mice, but not in CB 2 −/− mice (23), and that increased CB 2 R expression in mouse brain attenuates cocaine self-administration and cocaine-enhanced locomotion (19). In addition, brain CB 2 Rs may be involved in several DA-related CNS disorders, such as Parkinson's disease (24), schizophrenia (25), anxiety (26), and depression (27). The cellular mechanisms underlying CB 2 R modulation of DA-related behaviors and diseases are unclear, however.…”
mentioning
confidence: 99%